Beyond the Visible Classroom: How Indonesia's Pancasila Student Profile Strengthening Project Program as Hidden Curriculum Enhances Students’ Collaboration, Character Formation, and Creativity - Wahyuningrum, Paulina Maria Ekasari; Winei, Agnes Angi Dian; Jumrio, Edy; Andriyanto, Yustinus Dwi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study analyzed how Indonesia's Pancasila Student Profile Strengthening Project (P5), as a hidden curriculum, contributes to collaborative abilities, character formation, and creativity enhancement. The research employed a mixed-method correlational design, collecting quantitative data from 60 junior high students across 10 schools in Palangkaraya through Likert questionnaires, complemented by qualitative interviews with 10 P5 coordinator teachers, analyzed using Pearson correlation and thematic analysis. Statistical analysis revealed significant positive correlations between P5 implementation and all outcomes: character development (r = .507, p < .001), collaboration skills (r = .610, p < .001), and creativity (r = .652, p < .001), representing large effect sizes with creativity showing the strongest association (42.5% explained variance). Qualitative findings confirmed P5 fosters collaborative interactions through group projects, authentic character development through real-world experiences involving responsibility and empathy, and enhanced creativity through interest-driven projects. The study concludes that P5 effectively functions as a hidden curriculum, developing Pancasila Student Profile characteristics through meaningful experiential learning that transcends conventional approaches, warranting continued policy support.